Transformational Party Leaders: Determinants of Leadership Style Assessment in Central and Eastern Europe - Gherghina, Sergiu (2025)
The literature discussing leadership style identifies great variation between contemporary party leaders. While much attention is devoted to their actions, portrayal in the media, and relationships with their followers, there is limited analysis of which factors make a party leader transformational or transactional. This article addresses this gap in the literature and seeks to identify the characteristics of the party leaders or of the party to which they belong which lead party members to evaluate them on the transactional–transformational continuum. It uses original survey data from a modified version of the Multifactor Leadership Questionnaire. The analysis includes 12 political parties with parliamentary representation from Bulgaria, Hungary, and Romania between 2004 and 2018. The findings illustrate that members perceive as more transformational the first leaders of the party, those who have won competitive internal elections, and those with extensive political experience within the party.